Effects on bonding of anti-reflective cracking solutions at the top bituminous interface of a small airport pavement: a laboratory and modeling study - TATARANNI, PIERGIORGIO; SANGIORGI, CESARE; SIMONE, ANDREA; VIGNALI, VALERIA; VIOLA, PIERPAOLO; DONDI, GIULIO (Kluwer Academic Publishers, 2016)
The maintenance of bituminous airport pavements is of high concern when the limited available time for interventions and the performance effectiveness of the adopted materials are considered. In many cases, due to their former military vo-cation, small airport pavements have robust, sound and durable foundations that seldom require deep interventions of maintenance. Thus, it is more often needed to rehabilitate the pavement bituminous surface layers to restore the functional characteristics of the runaway and to protect the bottom layers from water leach-ing through the surface damages (e.g. cracks). This paper shows an example of airport pavement maintenance that was designed to rehabilitate the wearing course of a cracked bituminous structure that was proven to have sufficient bear-ing capacity. In order to prevent the reflection of cracks on the new layer, the ef-fects of using both a geosynthetic net and a Stress Absorbing Membrane Interlay-er (SAMI) were investigated at the old-new materials interface. The effects of debonding and the potential risk of slippage or delamination of the new wearing course were assessed by means of laboratory direct shear tests and multilayer elastic pavement system modeling.